CEO turnover and the new leader propensity to open innovation: Agency-resource dependence view and social identity perspective. Issue 6 (11th June 2018) - Biscotti, Anna Maria; Mafrolla, Elisabetta; Giudice, Manlio Del; D'Amico, Eugenio
Abstract : Purpose: In an increasingly turbulent and competitive environment, open innovation could be critical for a firm's success, favoring organizational flexibility and accelerating innovation processes. However, sharing innovation projects with external partners often requires changes in traditional organizational behavior and visions of CEOs. The purpose of this paper is to theorize and empirically verify how the CEO turnover and some socially relevant characteristics of the old and the new CEO may impact firms' propensity toward open innovation under an integrated agency-resource dependence view and social identity perspective. Design/methodology/approach: The empirical analysis was carried out on 264 companies drawn from 16 developed European markets included in the S&P Europe 350 Dow Jones index over the years 2006-2015. To test the predictions, the authors adopted regression analysis by employing the panel two-stages least squares model and the ordinary least squares econometric model. Findings: Consistently with the predictions, the authors found that CEO turnover stimulates open innovation. Particularly, the results suggest that the organizational identity rationale may motivate a divergent propensity between insider and outsider new CEOs, with outsiders more prone to open innovation. The higher tendency of new outsider CEOs to undertake innovation projects jointly with external organizations prevails also within firms that experienced a long tenure of the former CEO, thereby suggesting that a new outsider CEO appears able to renovate corporate strategic directions also in highly orthodox organizational cultures. Originality/value: To the best of the authors' knowledge, this is the first study that theorizes why CEO turnover might impact the propensity of the firm toward open innovation. The authors use an integrated agency-resource dependence perspective, and the results from the empirical analysis mostly support the predictions. Moreover, the authors adopt the social identity theory to show that the organizational identification of the CEO matters in the decision of engaging in open innovation.